Evaluation of Two Osmosis-Based Methods for the Preparation of Drug Delivery Systems Based on Red Blood Cells - Carmen Gutierrez-Millan; Celia Barez Diaz; Lydia Alvarez Vizan; Clara I. Colino (MDPI AG, 2023)
Erythrocytes have been thoroughly investigated as drug delivery systems for a wide range of therapeutic molecules and using different kinds of loading methods, outstanding the osmosis-based methods as the most used ones. Most of them involve too much handling of blood components and the immediate obtention of fresh blood. Based on our group's considerable experience in dialysis-based carrier erythrocyte preparation, this study details a simple method based on hypotonic dilution and subsequent resealing that has been developed for stavudine using packed erythrocytes from a local blood bank. Properties of the obtained carrier erythrocytes were studied in comparison to those prepared by dialysis. Erythrocytes' morphology, osmotic fragility, hematological parameters, and in vitro release profiles were evaluated. Loaded erythrocytes obtained with the proposed method did not show impaired properties in comparison with those obtained with our reference method, provided that the buffer composition remained the same. In the present work, we have optimized a simplified method for erythrocytes' drug loading, which can use blood transfusion products and could be easily automatized and scalable.